Emissions of ammonia following glyphosate application on Urochloa decumbens - V. Damin; P.C.O. Trivelin; J.A. Bonassi; A.C. Vitti (Plant, Soil and Environment, 2016)
This work was carried out with the objective of evaluating the ammonium (NH4+) levels and emissions of ammonia (NH3) after glyphosate application on signal grass (Urochloa decumbens). Two experiments were carried out and the following treatments were used: (1) Control - mechanic harvest with no herbicide application on signal grass; (2) Glyphosate - signal grass desiccation with the herbicide glyphosate. Ammonium (NH4+); total nitrogen (Ntot) levels in plant's tissues (experiment 1) and ammonia (NH3) emission by the plants or the soil (experiment 2) were evaluated over time, under field conditions. Signal grass desiccation with the herbicide glyphosate enhanced NH4+ levels from 2-24% of the Ntot at 12 days after herbicide application. The cumulative NH3 emission by leaves were increased from 2.8-5.3 kg/ha 30 days after herbicide application. Glyphosate application increases NH3 losses by plant, but it does not affect the NH3 emissions by soil, the dry mass production and Ntot in the aboveground portion of signal grass.